Overexpression of the SARS‐CoV‐2 receptor ACE2 is induced by cigarette smoke in bronchial and alveolar epithelia. Issue 1 (27th October 2020) - Liu, Aibin; Zhang, Xin; Li, Ronggang; Zheng, Mingzhu; Yang, Shasha; Dai, Longxia; Wu, Anhua; Hu, Chengping; Huang, Yanming; Xie, Mingxuan; Chen, Qiong
Abstract: Angiotensin‐converting enzyme 2 (ACE2) has been identified as the functional receptor of severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) and a target for disease prevention. However, the relationship between ACE2 expression and its clinical implications in SARS‐CoV‐2 pathogenesis remains unknown. Here, we explored the location and expression of ACE2, and its correlation with gender, age, and cigarette smoke (CS), in a CS‐exposed mouse model and 224 non‐malignant lung tissues (125 non‐smokers, 81 current smokers, and 18 ex‐smokers) by immunohistochemistry. Moreover, the correlations of ACE2 with CS‐induced oxidative stress‐related markers, hypoxia‐inducible factor‐1α (HIF‐1α), inducible nitric oxide synthase (iNOS), and 4‐hydroxynonenal (4‐HNE) were investigated. Chromatin immunoprecipitation and luciferase reporter assays identified the cause of ACE2 overexpression in human primary lung epithelial cells. We demonstrated that ACE2 was predominantly overexpressed on the apical surface of bronchial epithelium, while reduced in alveolar epithelium, owing to the dramatically decreased abundance of alveolar type II pneumocytes in CS‐exposed mouse lungs. Consistent with this, ACE2 was primarily significantly overexpressed in human bronchial and alveolar epithelial cells in smokers regardless of age or gender. Decreased ACE2 expression was observed in bronchial epithelial cells from ex‐smokers compared with current smokers, especially in those who had ceased smoking for more than 10 years. Moreover, ACE2 expression was positively correlated with the levels of HIF‐1α, iNOS, and 4‐HNE in both mouse and human bronchioles. The results were further validated using a publicly available dataset from The Cancer Genome Atlas (TCGA) and our previous integrated data from Affymetrix U133 Plus 2.0 microarray (AE‐meta). Finally, our results showed that HIF‐1α transcriptionally upregulates ACE2 expression. Our results indicate that smoking‐induced ACE2 overexpression in the apical surface of bronchial epithelial cells provides a route by which SARS‐CoV‐2 enters host cells, which supports clinical relevance in attenuating the potential transmission risk of COVID‐19 in smoking populations by smoking cessation. © 2020 The Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.